A hygro-thermo-chemical analysis of concrete at an early age and beyond under dry-wet conditions based on a fixed model. (December 2017) - Zhou, Wei; Qi, Tianqi; Liu, Xinghong; Feng, Chuqiao; Yang, Shuhan
Highlights: Heat transfer and moisture transport can be described for concrete at different age; The prediction values of the heat liberation rate correspond to theoretical results; The predicted humidity can embody the characteristics of the two-stage process. Abstract: Based on a fixed hygro-thermo-chemical model that is clearly distinguishable from other models in the existing literature, this work conducts a finite element analysis of heat transfer and moisture transport for concrete at an early age and beyond. Numerical validations show that this fixed model corresponds to the hydration heat liberation rate for ordinary Portland cement and reflects the two-phase process of the relative humidity changes. Simulations of concrete samples with various water-cement ratios are performed, and the outcomes are compared to experimental temperature and relative humidity curves, confirming that the modified model has relatively high accuracy. The simulated influential depths of moisture transfer in concrete are also in accordance with the results from theoretical equations.